EPIDEMIOLOGY OF BURNS IN MANIPAL - 5 YEAR RETROSPECTIVE STUDY (Journal of Forensic Medicine & Toxicology, 2013)
Material consists of all the patients admitted in the Burns Ward under department of plastic surgery in Kasturba Medical College hospital, this report describes the statistical analysis of 303 burns patients treated between January 2005 to December 2010. The analysis include age, sex, occupation, time of burn, total body surface area burnt, anatomical area involved, In our study Male formed 58.1 percent and female formed 41.9 percent of the total burns sustained. Highest incidence of burn amongst both males and females was in the age group of 21 to 30 years. In females the maximum number of burns occurred during 6 - 9 pm of the day whereas in males the maximum number of burns occurred during 3 - 6 pm. Maximum numbers of cases (117) were seen in winter, followed by 98 cases in summer and 88 cases in monsoon. Sixty seven cases had less than 10% of Body Surface Area involved. House wives and school children accounted for 54.1% of total admission. Skilled workers comprising of electrician, clerk, service people accounted for 14.9%, semiskilled workers comprised of laborers, mechanics, accounted for 22.8% and farmers accounted for 5% of total admission.
Keywords: Burns; Burn area; Occupation.